Design and Development of Material Requirement Planning (MRP)Tool for an Electronic Product Manufacturer - Abdullah, Rohana; Mohamad, Nor Akramin; Abdul Rahman, Mohd Soufhwee (2011)
Material Requirement Planning (MRP) has been widely used in the manufacturing industries as a tool to determine the purchase of the correct components in order to meet the delivery date of the customer demand. The current method to plan material purchases has caused the company various material discrepancies and human errors are unavoidable. Therefore, the aim of this project is to design and develop a MRP system to improve the efficiency of the material planning and ordering process. Databases were developed using extensive data on Bill of Material (BOM), inventory, lot sizes and customer demand and were integrated to produce a report on planned order release for the purchasing department to execute. In addition, the MRP system is also able to provide information regarding the capability of the production line to complete the customer demand on time.